Une architecture de cadres - Laurence Kimmel (Projets de Paysage)
Dani Karavan’s sculpture work for the Garden of Memories in Duisburg involves taking apart the existing buildings to maintain only their structure, which is painted in white. This process gives the structures an abstract quality, allowing them to be perceived as a three-dimensional framing of the environment. The multiple frames create many images, producing the effect of a signifying “constellation,” in reference to Walter Benjamin. Karavan became familiar with Benjamin‘s philosophy, while creating a memorial in his honor in Portbou (Spain) in 1991-94. We will examine the foundations of this experience within the aesthetics of the 19th century as well as its contemporaneity, as a pathway for the construction of perceptions through multiple frames and images.